Effect of aorto‐ventricular angulation on procedural success in transcatheter aortic valve replacements with the Lotus Valve system. Issue 7 (6th December 2017) - Rashid, Hashrul N.; McCormick, Liam M.; Talman, Andrew H.; Ihdayhid, Abdul R.; Nerlekar, Nitesh; Amiruddin, Ameera S.; Cameron, James; Nasis, Arthur; Meredith, Ian T.; Gooley, Robert P.
Abstract: Objective: To determine the effect of aorto‐ventricular angulation (AA) on procedural success with the Lotus Valve system. Background: AA, the angulation of the aortic valve basal plane, may affect the deployment of transcatheter aortic valve replacements (TAVRs). The Lotus Valve system is fully repositionable and delivered on a pre‐shaped catheter which may alter the impact of AA on its deployment. The effect of AA on procedural and clinical outcomes with the Lotus valve is unreported. Methods: Consecutive patients who underwent transfemoral TAVR with the Lotus Valve system were analyzed. AA was determined on pre‐procedural multi‐detector computed tomography imaging. Device success, procedural characteristics, and clinical events were assessed according to Valve Academic Research Consortium‐2 (VARC2) definitions. Results: One hundred sixty‐five patients were analyzed (48% male, mean age 84 years). The mean AA was 47.8 degrees. Patients were, therefore, divided into low AA (AA < 48°) or high AA (AA ≥ 48°). Baseline characteristics were similar in both cohorts. Device success and procedural outcomes were also similar including procedure time, contrast dose, and need to reposition. There was no difference in degree of moderate or greater para‐valvular regurgitation (PVR) (0% vs. 3%, P  = 0.09). Clinical outcomes of death, stroke, myocardial infarction, and other major VARC2 endpoints were similar. Conclusion: AA did not affect device success or clinical outcome with the Lotus Valve system. The Lotus' unique design features may have mitigated the impact of AA by improving the accuracy, ease of valve positioning, and reducing PVR.